Exploring Socio-Economic and Socio-Psychological Factors as A Predictor of Self-Help Groups Dynamics Effectiveness in Debre Birhan, Ethiopia - Wassie, Nebeyu Yohannes; Abebe, Daniel Tefera (LPPM Universitas Yudharta Pasuruan, 2024)
The study intended to address a knowledge gap by examining the group dynamics effectiveness of Self Help Groups in the Ethiopian context. A correlational design was applied and 372 Self Help Groups members were selected from 60 SHGs through simple random sampling. The main data analysis methods used were Pearson's product-moment correlation and multiple regression. The result indicated that the attitude (r=.667, p<001), extension contact (r=.534, p<001), socioeconomic profile (r=.593, p<001), and social participation (r=.400, p<001) of SHG members had a statistically significant positive relationship with the group’s performance. The model (attitude, social participation, socioeconomic profile, and extension contact) significantly predicted and explained 59.3% of the variance in self-help group dynamics effectiveness. Attitude was the strongest predictor (β = .512, p < .001) & uniquely explained 18.5% of the variance in group dynamics effectiveness, while the socioeconomic profile of self-help group members was the least predictor (β = .106, P < .005) with 0.5% of unique contribution in the explanation of group dynamics. The findings further revealed striking similarities with studies in Asia, suggesting that the potential universalities and the function of self-help group dynamics may transcend regional boundaries.